Structure and Responsibilities of Corporate Boards in Libyan Commercial Banks: Insights from Institutional Theory - زاقوب على (Dirasat in Economics and Business, 2015)
Research Purpose: This research uses a new institutional sociology perspective to investigate how different types of institutional pressures have influenced structure and responsibilities of corporate boards in Libyan commercial banks (LCBs). Design/Methodology/Approach: For this purpose, two pieces of empirical work, semi-structured interviews and a questionnaire survey were conducted respectively. The interviews were held with a number of stakeholders to ascertain their views on corporate governance in LCBs. A questionnaire survey were conducted to examine whether the ownership structure or any other factors have affected the governance practices of these banks and whether certain features have been institutionalized. Research Findings: The findings illustrate that different types of institutional pressures are shaping the current corporate boards practices and reforms in LCBs, especially coercive pressure from the Libyan Bank Law requirements and the Central Bank of Libya (CBL). The influences of these institutional pressures, to some extent, are deferent between LCBs according to the ownership structure, making some differences in responding to institutional pressures, and thus in corporate boards practices. Research limitations: the limitations are concerned with the research methods used in this research. For example, some participants in the interviews or questionnaire survey may have misinterpreted or not understood some of the questions because they are not familiar with them and do not want to show their lack of knowledge and thus they may not provide realistic answers. Moreover, in such research methods, the analysis of respondents’ answers depends, to some extent, on the researcher’s perspective and assessment, which can be more impressionistic and subjective. All these limitations mentioned above must be taken into account when using these findings. Research Implications: This research provides empirical evidence for understanding the New Institutional Sociology perspective of how different types of institutional pressures (coercive, normative and mimetic pressures) influence and shape the board practices in LCBs. This research suggests new avenues of research by focusing more on the impact of institutional pressures over the institutionalizing process of board practices and corporate governance practices. Practical Implications: This research helps the CBL as a regulator and policy maker of LCBs by identifying institutional factors affecting corporate governance practices in LCBs, and suggest how these practices can be improved.Originality/Value: The main contribution made by this research is the use of a new institutional sociology perspective as a theoretical framework to interpret the findings, since such a perspective has not been used frequently by researchers in the corporate governance literature. In this regard, the research provides a general understanding of how different types of institutional pressures (coercive, normative and mimetic pressures) influence and shape the current practices of corporate governance in LCBs. Moreover, it provides evidence about whether such institutional pressures influence LCBs similarly or differently according to their different ownership structure.